Rancang Bangun WSN berbasis nRF24L01 dan SIM800l bertenaga Surya untuk Implementasi IoT secara Outdoor - Wirarama Wedashwara; Budi Irmawati; Andy Hidayat Jatmika; Ariyan Zubaidi (Universitas Hamzanwadi, 2021)
Internet of things (IoT) requires an internet network for data communication between machines. Wifi is not always available outdoors and requires more portable data communication. This study aims to design a prototype Wireless Sensor Network (WSN) based on nRF24L01 and solar-powered SIM800l for outdoor IoT implementation. The study used a total of five IoT devices with four nodes with nRF24L01 and one node with nRF24L01 and SIM800l. Each device uses an Arduino nano, TP4056, 6WP solar panel, and a 900mAh 18650 battery. The evaluation of the system includes a comparative QoS analysis, namely packet delivery ratio (PDR), throughput, and delay in star and bus topology through data collection of observation methods by sensors. The evaluation results show that for unidirectional data communication the star topology has better results with PDR 99,099%, throughput 99.393%, and delay 0.0095s. While the bus topology produces a slight difference in PDR 98.766%, throughput 98.461%, and delay 0.017s. Evaluation of energy availability shows that during the day with an average voltage of 3.703v and at night 2.976v, there is no significant difference. During the day it produces 99.301% PDR, 99.653% throughput, and 0.001s delay, while at night it produces 94.221% PDR, 99.881% throughput, and 0.027s delay.